The Psychological Impact of COVID-19 Among Pakistani Adults in Lahore - Majeed, Saima; Schwaiger, Elizabeth Maria; Nazim, Abia; Samuel, Ivan Suneel (Frontiers in Public Health, 2021)
Background: In the wake of the worldwide spread of the novel coronavirus and the resultant restrictive measures, mental health has become a crucial issue. Physical health is not the only aspect of humans that is at risk. Globally, the rates and severity of mental illness are being significantly impacted by this pandemic. Two scales have been validated to measure the impact of coronavirus disease 2019 (COVID-19) on the levels of anxiety and obsessional thinking in clinical and non-clinical populations. The present study was designed to investigate the levels of anxiety and obsessions related to COVID-19 in the general public of Lahore, Pakistan. Materials and Methods: Data were collected via snowball sampling from May 9 to May 19. An online survey consisting of a demographic profile and two scales, Coronavirus Anxiety Scale (CAS) and Obsession with COVID-19 Scale (OCS), was sent through email, WhatsApp, and Facebook groups to adults (18 years and above) of Lahore, Pakistan. Results: A total of 240 individuals (20% men and 80% women) recorded their responses. The majority belonged to a nuclear family system (60%), and their education level ranged from high school to Ph.D. The cut-off score for probable dysfunctional coronavirus anxiety and obsession levels was not met within this sample (CAS, M = 3.24, SD = 4.21; OCS, M = 4.14, SD = 3.15), suggesting that the general population of Lahore, Pakistan is not suffering from dysfunctional anxiety or obsessions related to COVID-19. Forty-seven participants' score on OCS and 35 participants' scores on CAS were above the cut-off, i.e., ≥7 and ≥9, respectively. The results of the correlation analysis showed a significant positive relationship (**p < 0.619) between anxiety and obsessions related to COVID-19. Conclusion: One important, yet surprising, conclusion of this study is that the average adult in Lahore does not show much anxiety or obsessions related to COVID-19. Other studies around the world using these measurement tools have indicated significantly high levels of both anxiety and obsessions related to COVID-19. These findings may demonstrate the resilience of Pakistanis or perhaps the lack of understanding of the seriousness of the situation.